2009
DOI: 10.1086/648427
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatisandNeisseria gonorrhoeaeTransmission from the Oropharynx to the Urethra among Men Who Have Sex with Men

Abstract: A more complete understanding of the risks of transmission of C. trachomatis and N. gonorrhoeae from oropharynx to urethra will help inform prevention and screening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 11 publications
2
58
3
1
Order By: Relevance
“…Infection of the urethra with chlamydia and gonorrhoea is also common in MSM, and is associated with a history of penetrative oral and anal sex, but prevalence has been found at similar levels in men reporting only oro-insertive sex (90). A recent retrospective Australian study suggested oral sex to be significantly associated with urethral gonorrhoea infection (and primary syphilis), but urethral chlamydia was more strongly associated with anal sex (91).…”
Section: Chlamydia and Gonorrhoeamentioning
confidence: 99%
“…Infection of the urethra with chlamydia and gonorrhoea is also common in MSM, and is associated with a history of penetrative oral and anal sex, but prevalence has been found at similar levels in men reporting only oro-insertive sex (90). A recent retrospective Australian study suggested oral sex to be significantly associated with urethral gonorrhoea infection (and primary syphilis), but urethral chlamydia was more strongly associated with anal sex (91).…”
Section: Chlamydia and Gonorrhoeamentioning
confidence: 99%
“…Marcus et al reported that of 227 heterosexual men whose only urethral exposure was fellatio in the prior 3 months, 8 (3.5%) had urethral CT detected by urine TMA [28]. Similarly, Bernstein et al reported that of 397 MSM whose only urethral exposure was fellatio in the prior 3 months, 19 (4.8%) had urethral CT detected by urine TMA, and urethral CT positivity was higher in human immunodeficiency virus-infected individuals (16% vs 3%) [29]. Both studies enrolled patients from a San Francisco STD clinic among whom condom use was very rare.…”
Section: Discussionmentioning
confidence: 97%
“…Studies suggest that OP CT is transmissible to genital sites [28,29], which justifies treating patients who have OP CT detected, irrespective of presence of symptoms. However, because studies have demonstrated that OP CT prevalence is very low with routine OP CT screening, routine OP CT screening is not justified in most clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Pharyngeal testing for N. gonorrhoeae should be performed in MSM who have received oral intercourse during that interval. Although pharyngeal C. trachomatis screening is not a recommendation, studies have described a propensity of pharyngeal C. trachomatis carriage to result in disease transmission to genital sites (17,18). More-frequent screening may be indicated per additional sexual risk factors.…”
mentioning
confidence: 99%